Product Defect Level Analysis Bone Plate with The Six Sigma Method and Fuzzy Failure Mode and Effect Analysis (F-FMEA) : Analisis Tingkat Kecacatan Produk Bone Plate dengan Metode Six Sigma dan Fuzzy Failure Mode and Effect Analysis (F-FMEA) - Rizkyllah, Arya Bagus; Aryanny, Enny (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Product quality plays a crucial role in influencing consumer decisions, particularly in the medical device industry. Specific Background: PT XYZ is a manufacturer of orthopedic and traumatology implants, where even minor defects can have serious implications. Knowledge Gap: However, limited research has been conducted on identifying and mitigating product defects within this specific manufacturing context using integrated quality improvement methods. Aims: This study aims to evaluate the level and causes of product defects in order to provide targeted recommendations for quality enhancement. Results: The analysis revealed that the most frequent defect occurred in the hole diameter of the implant, with a total of 455 defective units. The process had a Defects Per Million Opportunities (DPMO) of 33,343 and an average sigma level of 3.33. The primary cause was the imprecise initial dimensions of the plate, resulting in a Fuzzy Risk Priority Number (FRPN) of 3.82. Novelty: The study uniquely integrates Six Sigma and Fuzzy Failure Mode and Effects Analysis (FMEA) to prioritize and address quality risks in a high-stakes manufacturing environment. Implications: It is recommended to implement raw material inspection prior to production to reduce defect rates and advance toward zero-defect manufacturing. Highlights: Identified critical defect in implant hole diameter. Integrated Six Sigma and Fuzzy FMEA for risk prioritization. Recommended raw material checks to reduce defects. Keywords: Product Quality, Six Sigma, Fuzzy FMEA, Orthopedic Implants, Defect Analysis